KURUMA: making car wash great / Nurul Hidayah Anuar ... [et al.] - Anuar, Nurul Hidayah; Abdul Rahman, Nur-Aini; Yusmandi, Fatin Syazwani; Awang Yaacob, Dayangku Nur Syahirah; Ujang, Rudy (Universiti Teknologi MARA, Kedah, 2024)
A mobile application called KURUMA brings together several vehicle wash service providers into a single, easily navigable platform, thereby revolutionizing the car wash sector. Convenience and efficiency are critical in today's hectic environment, and KURUMA meets these needs by providing car owners with an easy-to-use platform for finding, scheduling, and paying for car wash services. The need for car wash services expands along with urbanization and the number of vehicles on the road, yet the sector is still fragmented and inefficient. By offering a complete solution that benefits both customers and car wash businesses, KURUMA seeks to close this gap. By integrating with services like Stripe and PayPal, the app will use state-of-the-art technology to provide strong search and filter capabilities, real-time availability updates, and safe payment alternatives. Moreover, KURUMA will make use of the Twilio API for prompt email and SMS notifications as well as the Google Maps API for location-based services. KURUMA will provide car wash operators with better visibility, client engagement, and tools for effective booking and payment management. By removing the effort of searching for and scheduling vehicle wash services, KURUMA will improve customer happiness through a seamless experience that is designed with the user in mind. Operators of car washes will profit from improved consumer feedback and streamlined processes, which will allow for ongoing service enhancement. With prospective growth opportunities such as loyalty programmes, membership programmes, and alliances with auto repair companies, KURUMA is well-positioned to establish new benchmarks in the car wash sector. KURUMA wants to become the preferred platform for car wash services by fixing the present inefficiencies and fragmentation and providing an excellent and effective experience for all parties involved.